(untitled) (International Journal of Engineering and Computer Science, 2015)
If the digital society is rooted in civil society, it does not duplicate. Indeed, a great number of social practices are put into place both in the real world as well as in the virtual world and are organized around the same objects: time and space; however, they differ in their realization. The Internet is at the crossroads of two phenomena that oppose one another with respect to both their concepts and the social practices involved; these are anonymity and privacy life. Quite clearly a number of phenomena have emerged from these different Internet approaches. So, what are the consequences of these new concepts of time and space on Internet?